Loosening of Bolted Connections under Transverse Loading in Timber Structures - Jiawei Chen (Forests, 2020)
Bolted joints are widely used in timber structures, and the loosening of bolt connections will reduce the structural performance. In this paper, a mechanical model of bolt connection for timber structures is established, and the process of bolt loosening under a transverse load is investigated. By using the finite element method to construct an accurate thread model with a helix angle, the thread contact state during the bolt loosening procedure was analyzed in detail, and the factors such as load amplitude, load frequency, load location, and different timber materials on bolt loosening are also studied. In the timber structure, the load amplitude is the main factor affecting the bolt loosening, the decay rate of the preload in the bolted joint is positively correlated with the amplitude of the cyclic transverse load. The frequency of the loading has a smaller effect on the looseness, the preload decreases as the frequency increases. When the load is applied to the smooth rod part of the bolt, the preload force will decrease rapidly, and the distance between the load position and the bolt has no effect on the change in looseness. The decreasing range of the preload is different with different timber material, but the decreasing law is the same. The model can be applied to analyze the loosening rule of bolted connections in timber structures.